Heterogeneous photo-Fenton process with zerovalent iron nanoparticles for degradation of toluene in aqueous solution - Clara Duca; Horacio Bogo; Marta I. Litter; Enrique San Román (Catalysis Communications, 2023)
Degradation of toluene by treatment with zerovalent iron nanoparticles and different H2O2 concentrations under UVA light has been analyzed at pH 3. The highest removal of toluene was found with 100 mg L−1 nZVI and 400 mg L−1 H2O2, but 100 and 200 mg L−1 of H2O2 were used in most experiments as the degradation rate was similar. Experiments with Fe(II) (10 and 1 mg L−1) were performed for comparison. Benzaldehyde and bibenzyl were found the main oxidation products. nZVI could be reused without loss of efficiency. A mechanism was proposed.